2004
DOI: 10.1002/cm.20039
|View full text |Cite
|
Sign up to set email alerts
|

Aurora‐C kinase is a novel chromosomal passenger protein that can complement Aurora‐B kinase function in mitotic cells

Abstract: The function of Aurora-C kinase, a member of the Aurora kinase family identified in mammals, is currently unknown. We present evidence that Aurora-C, like Aurora-B kinase, is a chromosomal passenger protein localizing first to centromeres and then to the midzone of mitotic cells. Aurora-C transcript is expressed at a moderate level albeit about an order of magnitude lower than Aurora-B transcript in diploid human fibroblasts. The level of Aurora-C transcript is elevated in several human cancer cell types. Auro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
226
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 251 publications
(239 citation statements)
references
References 29 publications
8
226
1
3
Order By: Relevance
“…Recently, it has been demonstrated that Aurora-C is a new member of the chromosomal passenger proteins interacting, similarly to Aurora-B, with INCENP and survivin, thus contributing to the regulation of chromosome segregation and cytokinesis 22,41 . In this context, it is worthwhile to mention that Aurora-B and C share the highest degree of sequence overlap with about 83% sequence identity whereas the kinases C and A share about 71% sequence identity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that Aurora-C is a new member of the chromosomal passenger proteins interacting, similarly to Aurora-B, with INCENP and survivin, thus contributing to the regulation of chromosome segregation and cytokinesis 22,41 . In this context, it is worthwhile to mention that Aurora-B and C share the highest degree of sequence overlap with about 83% sequence identity whereas the kinases C and A share about 71% sequence identity.…”
Section: Discussionmentioning
confidence: 99%
“…Aurora C was shown to localize like a chromosomal passenger protein, but it is expressed at lower levels than Aurora B and might be func- tionally redundant with Aurora B (Li et al, 2004;Sasai et al, 2004). However, simultaneous knockdown of INCENP and Aurora C or INCENP, Aurora C, and Aurora B followed by rescue with GFP-INCENP 1-58 resulted in centromere localization of the ternary INCENP 1-58 -Survivin-Borealin complex, excluding a compensatory role for Aurora C (Supplemental Figure S2, middle and bottom rows).…”
Section: Ectopic Gfp-incenp 1-58 Can Target Survivin and Borealin Butmentioning
confidence: 99%
“…1D) and the overexpression of Aurora-C-WT has no significant effects. 6,7,9,16 In contrast, ectopic expression of Aurora-C-T191D specifically induces morphological changes in U2OS cells (Fig. 1D).…”
mentioning
confidence: 94%
“…4,5 Overexpression studies with Aurora-C suggest that it has overlapping functions with Aurora-B in mitosis and with Aurora-A in interphase. [6][7][8][9] Because the three mammalian Aurora paralogues are very similar in sequence, it is possible that these results are artificial and do not represent the true physiological functions of Aurora-C. So far, the studies were mainly based on the ectopic expression of kinase-inactive Aurora-C mutants and Aurora-C-WT.…”
mentioning
confidence: 99%
See 1 more Smart Citation